Official visit of UMP delegation to MMU Cyberjaya explores strategic collaboration - Mimi Rabita, Abdul Wahit (2023)
CYBERJAYA, 19 December 2022 - The visit of the Universiti Malaysia Pahang (UMP) delegation to Multimedia University (MMU) aimed to establish a joint venture and share resources in terms of academics, technology, expertise and others.